Preparation method of oxide and sulfide composite positive electrode material and solid-state battery

By using the preparation method of oxide and sulfide composite positive electrode material in solid-state batteries, a stable composite cladding layer is formed, which solves the problem of unstable interface between the positive electrode material of solid-state battery and the solid-state electrolyte of sulfide, and significantly improves the performance and cycle life of the battery.

CN119905555APending Publication Date: 2025-04-29ZHONGKE RONNENG (YANCHENG) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411966029.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The contact interface between the positive electrode material of the existing solid-state battery and the solid electrolyte of the sulfide is unstable, resulting in a degradation of battery performance. The traditional improvement method is cumbersome and has poor results.

Method used

The preparation method of oxide and sulfide composite positive electrode material is adopted to form a stable composite cladding layer through the pretreatment of the positive electrode material, oxide solid electrolyte coating, sulfide solid electrolyte coating, sintering treatment and solid battery assembly steps, and the interface stability between the positive electrode material and the solid electrolyte is improved.

Benefits of technology

It effectively improves the interface stability between the positive electrode material and the solid electrolyte, reduces interface side reactions, improves the performance and cycle life of the battery, enhances the ionic conductivity of the oxide solid electrolyte layer, and improves the rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905555A_ABST
    Figure CN119905555A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an oxide and sulfide composite positive electrode material. The preparation method specifically comprises the following steps: S1, pretreating a positive electrode material; s2, coating the oxide solid electrolyte; s3, coating a sulfide solid electrolyte; the invention relates to the technical field of solid-state batteries. According to the preparation method of the oxide and sulfide composite positive electrode material and the solid-state battery, through composite coating modification of the peroxide and sulfide solid-state electrolyte, the interface stability between the positive electrode material and the solid-state electrolyte is effectively improved, the interface side reaction is reduced, the performance of the battery is improved, and the cycle life of the battery is prolonged; the oxide solid electrolyte layer has high ionic conductivity and can accelerate diffusion of lithium ions and improve the rate capability of the battery, and the preparation method is simple and efficient in process, low in raw material cost, low in energy consumption, environment-friendly and convenient for industrial production. The material has the advantages of high energy density, long cycle life, high safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for preparing an oxide and sulfide composite positive electrode material and a solid-state battery. Background Art

[0002] A solid-state battery is a battery that uses solid electrodes and solid electrolytes. The negative electrode material of a solid-state battery can be a composite negative electrode of nano-silicon and graphite, and the positive electrode can be lithium manganese oxide, a lithium-rich manganese-based material, or a lithium-free positive electrode material. The electrolyte is a solid electrolyte with an energy density of 300-450 watt-hours / kilogram. Solid-state batteries use solid electrolytes to replace the electrolytes and diaphragms of traditional lithium-ion batteries. They are safer, have higher energy density, and have stronger cycle performance. They have become the main research and development direction of the next generation of power batteries. Solid electrolytes can be roughly divided into three categories: inorganic electrolytes, solid polymer electrolytes, and composite electrolytes. Since the power-to-weight ratio of solid-state batteries is relatively high, they are ideal batteries for electric vehicles.

[0003] With the rapid development of electric vehicles and energy storage systems, solid-state batteries have attracted much attention due to their advantages such as high energy density, long cycle life and high safety. However, solid-state batteries still face some challenges in practical applications, such as the interface instability between the solid-state electrolyte and the cathode material and the insufficient ionic conductivity of the solid-state electrolyte. These problems limit the large-scale application of solid-state batteries.

[0004] Existing solid-state battery positive electrode materials, such as NMC (811) positive electrode materials, have the advantages of high capacity and low cost, but the contact interface with sulfide solid electrolyte is unstable, resulting in a decrease in battery performance. Traditional improvement methods, such as preparing coating layers, are cumbersome and ineffective. Therefore, developing a simple and efficient coating modification method to improve the interface stability between the positive electrode material and the solid electrolyte has become a technical problem that needs to be urgently solved in the field of solid-state batteries. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing an oxide and sulfide composite positive electrode material and a solid-state battery, which solves the problems mentioned in the above background technology.

[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for preparing an oxide and sulfide composite positive electrode material, specifically comprising the following steps:

[0007] S1. Pretreatment of positive electrode materials: grinding, sieving and drying the positive electrode active materials, and then drying them by vacuum drying at a temperature of 40-120° C. for 1-24 hours to obtain positive electrode material particles with a particle size of 5-15 μm, and then compounding the positive electrode active materials with a polymer electrolyte;

[0008] S2. Oxide solid electrolyte coating: dissolving a specific oxide solid electrolyte in a solvent to form an electrolyte solution, and evenly coating the electrolyte solution on the surface of the positive electrode material particles by spin coating. Finally, removing ethanol by baking to obtain a positive electrode material coated with an oxide solid electrolyte;

[0009] S3, sulfide solid electrolyte coating: the sulfide solid electrolyte material is formed into electrolyte particles through a dry process, and then the electrolyte particles are mixed with the positive electrode material coated with the oxide solid electrolyte, and the composite positive electrode material coated with the sulfide solid electrolyte is obtained by grinding and granulating;

[0010] S4, sintering treatment: the composite positive electrode material coated with the sulfide solid electrolyte is sintered at high temperature, the sintering conditions are: keeping the temperature at 300°C for 3-5h, then heating to 800-1000°C for 5-10h, the heating method is programmed heating, and the heating rate of the programmed heating is 5-10°C / min, so that the oxide and sulfide solid electrolyte layers are closely combined with the positive electrode material to form a stable composite coating layer;

[0011] S5. Solid-state battery assembly: The composite coated modified positive electrode material, solid electrolyte layer and lithium metal negative electrode are stacked in sequence to form a multi-layer battery cell structure. Then, the battery cell is sealed and packaged using packaging equipment to obtain a solid-state battery.

[0012] Preferably, in S1, the positive electrode active material is LiNiCoMnO2 or LiNi o.8 Co o.1 Mo o.1 O2, the polymer electrolyte includes an organic solvent, a lithium salt and a polymer compound.

[0013] Preferably, the organic solvent is selected from at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide and 1,3-dioxolane; the lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium bis(trifluoromethanesulfonyl)imide; and the polymer compound is selected from at least one of polyethylene oxide, polypropylene carbonate, polyethylene carbonate, polyvinylene carbonate, polytrimethylene carbonate, polycaprolactone, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl methacrylate, succinonitrile, polysiloxane and polyurethane.

[0014] Preferably, in S2, the oxide solid electrolyte includes at least one of a perovskite-type oxide solid electrolyte, a sodium superion conductor-type oxide solid electrolyte, a lithium superion conductor-type oxide solid electrolyte and a garnet-type oxide solid electrolyte.

[0015] Preferably, in S3, the sulfide solid electrolyte includes at least one of a perovskite sulfide solid electrolyte, a sodium superion conductor sulfide solid electrolyte, a lithium superion conductor sulfide solid electrolyte and a garnet sulfide solid electrolyte.

[0016] A solid-state battery comprises a battery positive electrode material, a negative electrode and a solid electrolyte layer prepared by the above preparation method, wherein the positive electrode adopts the above composite coated modified positive electrode material, the negative electrode adopts lithium metal or alloy, and the solid electrolyte layer adopts a sulfide solid electrolyte material.

[0017] Beneficial Effects

[0018] The present invention provides a method for preparing a composite positive electrode material of oxide and sulfide and a solid-state battery. Compared with the prior art, the present invention has the following beneficial effects: the method for preparing a composite positive electrode material of oxide and sulfide and the solid-state battery specifically include the following steps: S1, pretreatment of positive electrode material; S2, coating of oxide solid electrolyte; S3, coating of sulfide solid electrolyte; S4, sintering treatment; S5, assembly of solid-state battery; through the composite coating modification of peroxide and sulfide solid electrolyte, the interface stability between the positive electrode material and the solid electrolyte is effectively improved, the interface side reaction is reduced, and the performance and cycle life of the battery are improved. The oxide solid electrolyte layer has a high ionic conductivity, can accelerate the diffusion of lithium ions, and improve the rate performance of the battery. The preparation method is simple and efficient, the raw material cost is low, the energy consumption is low, the environment is friendly, and it is easy to industrialize. The prepared solid-state battery of the positive electrode material has the advantages of high energy density, long cycle life and high safety, and can meet the needs of electric vehicles and energy storage systems for high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] See also Figure 1The present invention provides three technical solutions: a method for preparing an oxide and sulfide composite positive electrode material, specifically including the following embodiments:

[0022] Embodiment 1

[0023] S1. Pretreatment of positive electrode materials: grinding, sieving and drying the positive electrode active materials, and then drying them by vacuum drying at a temperature of 80° C. for 12 h to obtain positive electrode material particles with a particle size of 10 μm, and then compounding the positive electrode active materials with a polymer electrolyte;

[0024] S2. Oxide solid electrolyte coating: dissolving a specific oxide solid electrolyte in a solvent to form an electrolyte solution, and evenly coating the electrolyte solution on the surface of the positive electrode material particles by spin coating. Finally, removing ethanol by baking to obtain a positive electrode material coated with an oxide solid electrolyte;

[0025] S3, sulfide solid electrolyte coating: the sulfide solid electrolyte material is formed into electrolyte particles through a dry process, and then the electrolyte particles are mixed with the positive electrode material coated with the oxide solid electrolyte, and the composite positive electrode material coated with the sulfide solid electrolyte is obtained by grinding and granulating;

[0026] S4, sintering treatment: the composite positive electrode material coated with the sulfide solid electrolyte is sintered at high temperature, the sintering conditions are: keeping the temperature at 300°C for 4 hours, then heating to 900°C for 7 hours, the heating method is programmed heating, and the heating rate of the programmed heating is 7°C / min, so that the oxide and sulfide solid electrolyte layers are closely combined with the positive electrode material to form a stable composite coating layer;

[0027] S5. Solid-state battery assembly: The composite coated modified positive electrode material, solid electrolyte layer and lithium metal negative electrode are stacked in sequence to form a multi-layer battery cell structure. Then, the battery cell is sealed and packaged using packaging equipment to obtain a solid-state battery.

[0028] Embodiment 2

[0029] S1. Pretreatment of positive electrode materials: grinding, sieving and drying the positive electrode active materials, and then drying them by vacuum drying at a temperature of 40° C. for 1 h to obtain positive electrode material particles with a particle size of 5 μm, and then compounding the positive electrode active materials with the polymer electrolyte;

[0030] S2. Oxide solid electrolyte coating: dissolving a specific oxide solid electrolyte in a solvent to form an electrolyte solution, and evenly coating the electrolyte solution on the surface of the positive electrode material particles by spin coating. Finally, removing ethanol by baking to obtain a positive electrode material coated with an oxide solid electrolyte;

[0031] S3, sulfide solid electrolyte coating: the sulfide solid electrolyte material is formed into electrolyte particles through a dry process, and then the electrolyte particles are mixed with the positive electrode material coated with the oxide solid electrolyte, and the composite positive electrode material coated with the sulfide solid electrolyte is obtained by grinding and granulating;

[0032] S4, sintering treatment: the composite positive electrode material coated with the sulfide solid electrolyte is sintered at high temperature, the sintering conditions are: keeping the temperature at 300°C for 3 hours, then heating to 800°C for 5 hours, the heating method is programmed heating, and the heating rate of the programmed heating is 5°C / min, so that the oxide and sulfide solid electrolyte layers are closely combined with the positive electrode material to form a stable composite coating layer;

[0033] S5. Solid-state battery assembly: The composite coated modified positive electrode material, solid electrolyte layer and lithium metal negative electrode are stacked in sequence to form a multi-layer battery cell structure. Then, the battery cell is sealed and packaged using packaging equipment to obtain a solid-state battery.

[0034] Embodiment 3

[0035] S1. Pretreatment of positive electrode materials: grinding, sieving and drying the positive electrode active materials, and then drying them by vacuum drying at a temperature of 120° C. for 24 h to obtain positive electrode material particles with a particle size of 15 μm, and then compounding the positive electrode active materials with the polymer electrolyte;

[0036] S2. Oxide solid electrolyte coating: dissolving a specific oxide solid electrolyte in a solvent to form an electrolyte solution, and evenly coating the electrolyte solution on the surface of the positive electrode material particles by spin coating. Finally, removing ethanol by baking to obtain a positive electrode material coated with an oxide solid electrolyte;

[0037] S3, sulfide solid electrolyte coating: the sulfide solid electrolyte material is formed into electrolyte particles through a dry process, and then the electrolyte particles are mixed with the positive electrode material coated with the oxide solid electrolyte, and the composite positive electrode material coated with the sulfide solid electrolyte is obtained by grinding and granulating;

[0038] S4, sintering treatment: the composite positive electrode material coated with the sulfide solid electrolyte is sintered at high temperature, the sintering conditions are: keeping the temperature at 300°C for 5 hours, then heating to 1000°C for 10 hours, the heating method is programmed heating, and the heating rate of the programmed heating is 10°C / min, so that the oxide and sulfide solid electrolyte layers are closely combined with the positive electrode material to form a stable composite coating layer;

[0039] S5. Solid-state battery assembly: The composite coated modified positive electrode material, solid electrolyte layer and lithium metal negative electrode are stacked in sequence to form a multi-layer battery cell structure. Then, the battery cell is sealed and packaged using packaging equipment to obtain a solid-state battery.

[0040] Effect Example

[0041] The solid-state batteries provided by Examples 1-3 and Comparative Example (conventional solid-state batteries on the market) were subjected to the following performance tests for capacity testing and cycle testing, and the test results are shown in the following table:

[0042]

[0043]

[0044] It can be seen from the above table that: through the composite coating modification of peroxide and sulfide solid electrolyte, the interface stability between the positive electrode material and the solid electrolyte is effectively improved, the interface side reaction is reduced, and the performance and cycle life of the battery are improved. The oxide solid electrolyte layer has a high ionic conductivity, which can accelerate the diffusion of lithium ions and improve the battery's rate performance. The preparation method is simple and efficient, the raw material cost is low, the energy consumption is low, it is environmentally friendly, and it is easy to industrialize. The solid-state battery of the prepared positive electrode material has the advantages of high energy density, long cycle life and high safety, and can meet the needs of electric vehicles and energy storage systems for high-performance batteries.

[0045] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0046] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an oxide and sulfide composite positive electrode material, characterized in that: The specific steps include: S1. Pretreatment of positive electrode materials: grinding, sieving and drying the positive electrode active materials, and then drying them by vacuum drying at a temperature of 40-120° C. for 1-24 hours to obtain positive electrode material particles with a particle size of 5-15 μm, and then compounding the positive electrode active materials with a polymer electrolyte; S2. Oxide solid electrolyte coating: dissolving a specific oxide solid electrolyte in a solvent to form an electrolyte solution, and evenly coating the electrolyte solution on the surface of the positive electrode material particles by spin coating. Finally, removing ethanol by baking to obtain a positive electrode material coated with an oxide solid electrolyte; S3, sulfide solid electrolyte coating: the sulfide solid electrolyte material is formed into electrolyte particles through a dry process, and then the electrolyte particles are mixed with the positive electrode material coated with the oxide solid electrolyte, and the composite positive electrode material coated with the sulfide solid electrolyte is obtained by grinding and granulating; S4, sintering treatment: the composite positive electrode material coated with the sulfide solid electrolyte is sintered at high temperature, the sintering conditions are: keeping the temperature at 300°C for 3-5h, then heating to 800-1000°C for 5-10h, the heating method is programmed heating, and the heating rate of the programmed heating is 5-10°C / min, so that the oxide and sulfide solid electrolyte layers are closely combined with the positive electrode material to form a stable composite coating layer; S5. Solid-state battery assembly: The composite coated modified positive electrode material, solid electrolyte layer and lithium metal negative electrode are stacked in sequence to form a multi-layer battery cell structure. Then, the battery cell is sealed and packaged using packaging equipment to obtain a solid-state battery.

2. The method for preparing an oxide and sulfide composite positive electrode material according to claim 1, characterized in that: In the S1, the positive electrode active material is LiNiCoMnO2 or LiNi o.8 Co o.1 Mo o.1 O2, the polymer electrolyte includes an organic solvent, a lithium salt and a polymer compound.

3. The method for preparing an oxide and sulfide composite positive electrode material according to claim 2, characterized in that: The organic solvent is selected from at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethylene glycol dimethyl ether, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide and 1,3-dioxolane; the lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium bis(trifluoromethanesulfonyl)imide; and the polymer compound is selected from at least one of polyethylene oxide, polypropylene carbonate, polyethylene carbonate, polyvinylene carbonate, polytrimethylene carbonate, polycaprolactone, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polymethyl methacrylate, succinonitrile, polysiloxane and polyurethane.

4. The method for preparing an oxide and sulfide composite positive electrode material according to claim 1, characterized in that: In S2, the oxide solid electrolyte includes at least one of a perovskite-type oxide solid electrolyte, a sodium superion conductor-type oxide solid electrolyte, a lithium superion conductor-type oxide solid electrolyte and a garnet-type oxide solid electrolyte.

5. The method for preparing an oxide and sulfide composite positive electrode material according to claim 1, characterized in that: In S3, the sulfide solid electrolyte includes at least one of a perovskite sulfide solid electrolyte, a sodium superion conductor sulfide solid electrolyte, a lithium superion conductor sulfide solid electrolyte and a garnet sulfide solid electrolyte.

6. A solid-state battery, characterized in that: It comprises a battery positive electrode material, a negative electrode and a solid electrolyte layer prepared by the preparation method as described in any one of claims 1 to 5, the positive electrode adopts the above-mentioned composite coated modified positive electrode material, the negative electrode adopts lithium metal or alloy, and the solid electrolyte layer adopts sulfide solid electrolyte material.